IMPACT OF FINANCIAL PERFORMANCE ON FIRM VALUE IN THE FOOD AND BEVERAGE SECTOR ON THE INDONESIA STOCK EXCHANGE - Sulaiman Kurdi; Arum Pujiastuti; Umi Hani (Journal Economic Insights, 2023)
Investors place a premium on a firm's value when making investments. This study intends to analyze the financial performance of the firm value of the food and beverage sector on the Indonesia Stock Exchange for the period of 2018 to 2021. Profitability, leverage, and liquidity ratios are the financial ratios used to measure financial performance. A total of 24 companies were selected using a method of purposive sampling based on specific criteria. Through the Stata software, a statistical test of data analysis was conducted using linear regression and a static panel approach. The study's findings demonstrate, with a confidence level of 1%, that profitability has a statistically positive impact on the value of a firm. While leverage and liquidity have no influence on a firm.